Optimization of Surface Smoothness of Nd1.12Ba1.88Cu3O7-δ Thin Films - Eko Hadi Sujiono (Institut Teknologi Bandung, 2007)
We explored the use of Nd1+xBa2-xCu3O7 (x = 0.12) as target material during sputter deposition. Adjustment of the growth parameters such as growth temperature and partial oxygen pressure on the effect of surface roughness, crystallinity, and electrical properties of thin films on SrTiO3 as well as MgO substrates have been studied. The microstructure of Nd1.12Ba1.88Cu3O7-δ thin films was observed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM). In order to reduce precipitation on the films, we use special SrTiO3 substrate treatment or applied a buffer layer on MgO substrates, resulting in smooth Nd1.12Ba1.88Cu3O7-δ thin films. Furthermore, the smoothness of a ramp-edge (created by Ar-ion beam etching) is studied. Structuring of the ramp in tri-layer of Nd1.12Ba1.88Cu3O7-δ/SrTiO3/PrBa2Cu3-xGaxO is performed using a standard photolithography process.